Wojna w eterze : wspomnienia - Nowak, Jan, 1913- (Krakow : ZNAK, 1991)
A memoir of a Polish radio journalist who worked for Radio Free Europe from 1948 to 1976.
t. 1. 1948-1956 -- t. 2. Polska z oddali : 1956-1976.
Vol. 2 has title: Polska z oddali.
Includes bibliographical references and index.
Keywords: Nowak, Jan, -- 1913-; Radio Free Europe -- Biography; Journalists -- Poland -- Biography; Poland -- Politics and government -- 1945-1980.; Poland -- Foreign relations -- 1945-1989.